Engklek dan Monopoli sebagai Media untuk Meningkatkan Perilaku Pengendalian Vektor DBD pada Siswa SD Negeri Karangjati, Bantul - Viska Herawati; Heru Subaris Kasjono; Sarjito Eko Windarso (Poltekkes Kemenkes Yogyakarta, 2018)
The effort to increase public health level can be obtained with clean and healthy live behaviors.Dengue Hemorrhagic Fever (DHF) is arisen from lack of knowledge and awareness about environmental health. Many ways can be done to improve controlling behavior of DHF vectors. Forelementary school children, one of them is by playing games. The purpose of this study was toknow the effectiveness of hopscotch and monopoly games as the information media to improvethe control behavior of DHF vectors among elementary school students, by conducting a quasiexperiment with non-equivalent control group design. The study was carried out on May 2018.The study subject was 45 third grade students of the State Elementary School in Karangjati,Bantul. The data was analyzed to test the score differences between pre-test and post test. Paired t-test was used for normally distributed data and Wilcoxon test for the not-normal ones. Theanalysis for testing the mean differences among study groups was one way Anova for normallydistributed data and Kruskal Wallis test for the not-normal ones. All statistic tests were at 95 %significance level. The results shows significant difference between pre-test and post test ofknowledge and attitude measurement of the hopscotch and monopoly groups (p<0,05); and alsosignificant difference between pre-test and post-test of practice of all treatments (p<0,05). Toconclude, the games are only effective to improve knowledge about controlling DHF vectors, andhopscotch game is the most effective media.